2021
DOI: 10.1002/pon.5780
|View full text |Cite
|
Sign up to set email alerts
|

Cancer care for people with mental disorders: A qualitative survey among cancer care and psychiatric care professionals in Japan

Abstract: Objective: It is widely assumed that there are multiple levels (from individual to policy level) of problems involving disparities in cancer care for people with mental disorders. However, few studies have comprehensively investigated issues as perceived by medical professionals. The purpose of the present study was to identify a wide range of issues in cancer care for people with mental disorders and offer corresponding solutions for both cancer care professionals and psychiatric care professionals. Methods:W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(39 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…Further effort is necessary to promote collaborations between cancer care providers and primary psychiatric care/welfare services. One solution may be to offer specific cancer care support for people with disabilities, including mental disorders, as part of patient support or palliative care centers at designated cancer hospitals 15 . Another solution is to establish region‐wide programs, which include case review meetings, which promote collaborative treatment for cancer patients with mental illnesses 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further effort is necessary to promote collaborations between cancer care providers and primary psychiatric care/welfare services. One solution may be to offer specific cancer care support for people with disabilities, including mental disorders, as part of patient support or palliative care centers at designated cancer hospitals 15 . Another solution is to establish region‐wide programs, which include case review meetings, which promote collaborative treatment for cancer patients with mental illnesses 15 …”
Section: Discussionmentioning
confidence: 99%
“…14 To identify issues of cancer treatment in people with mental disorders, we previously conducted a qualitative survey in multidisciplinary healthcare professionals. 15 In the survey, we extracted the following issues faced by cancer care providers: 'cancer health care professional's knowledge and attitude towards people with mental disorders'; 'coordination between psychiatric care professionals and cancer care professionals'; and 'the issue of designated cancer hospitals.' It remains unclear which issues are perceived by cancer care providers as difficult/insufficient.…”
Section: Introductionmentioning
confidence: 99%
“…The study found that there were barriers to cancer care provision for patients affected by SMI: fragmentation of care; healthcare providers' understanding of SMI; complex nature of presentation; and specialized care needs. In a Japanese study, by analyzing the responses of 439 professionals, Etoh et al 23 A very specific and important point was raised by McFarland et al 25 in the USA. In a series of psychiatric consultations for patients with SMI and cancer, they found that shared decision making was often a problem.…”
Section: Stigma Marginalization and Communication Problemsmentioning
confidence: 99%
“…The study found that there were barriers to cancer care provision for patients affected by SMI: fragmentation of care; healthcare providers' understanding of SMI; complex nature of presentation; and specialized care needs. In a Japanese study, by analyzing the responses of 439 professionals, Etoh et al 23 . categorized issues related to communication barriers into a series of dimensions: patient factors; isolation and lack of support; attitudes of both psychiatry and cancer care professionals.…”
Section: Overview Of the Special Issue Contentmentioning
confidence: 99%
“…For example, patients may experience diagnosis or treatment delays, have difficulties in adhering to or receipt of appropriate cancer treatment because of the symptoms of mental disorders. 8,9 Poorer adherence could lead to those individuals with PMHD not being allocated to recommended treatment pathways. Therefore, the important questions about the management of cancer in the context of PMHD are to what extent patients experience treatment delays or receive different/less effective treatment regimens compared to those without PMHD.…”
Section: Introductionmentioning
confidence: 99%